Isolation of a Hypomorphic skn-1 Allele That Does Not Require a Balancer for Maintenance. Issue 3 (1st March 2016) - Tang, Lanlan; Dodd, William; Choe, Keith
Abstract: In Caenorhabditis elegans, the transcription factor SKN-1 has emerged as a central coordinator of stress responses and longevity, increasing the need for genetic tools to study its regulation and function. However, current loss-of-function alleles cause fully penetrant maternal effect embryonic lethality, and must be maintained with genetic balancers that require careful monitoring and labor intensive strategies to obtain large populations. In this study, we identified a strong, but viable skn-1 hypomorphic allele skn-1 ( zj15 ) from a genetic screen for suppressors of wdr-23, a direct regulator of the transcription factor. skn-1 ( zj15 ) is a point mutation in an intron that causes mis-splicing of a fraction of mRNA, and strongly reduces wildtype mRNA levels of the two long skn-1a/c variants. The skn-1 ( zj15 ) allele reduces detoxification gene expression and stress resistance to levels comparable to skn-1 RNAi, but, unlike RNAi, it is not restricted from some tissues. We also show that skn-1 ( zj15 ) is epistatic to canonical upstream regulators, demonstrating its utility for genetic analysis of skn-1 function and regulation in cases where large numbers of worms are needed, a balancer is problematic, diet is varied, or RNAi cannot be used.